Why some pregnant women refuse glucose challenge test? Turkish pregnant women's perspectives for gestational diabetes mellitus screening - AKDENİZ, ESRA (KARE PUBL, 2018)
OBJECTIVE: Diabetes in pregnancy is associated with several adverse outcomes for both mother and baby. Awareness is the first step toward identifying pregnant women with diabetes. The purpose of this study was to assess Turkish pregnant women's opinion and practice about 50-g glucose challenge test (GCT) and to assess the reasons why some of them refuse the test. METHODS: This study was conducted on 312 patients at any age and gestational week in Istanbul, Turkey, by a personal interview using self-created questionnaire. Women were asked about their opinion and practice about 50-g GCT. RESULTS: Among women who were <= 28 weeks of gestation, 42.5% (n = 82/193) exhibited their desire to have a GCT in their ongoing pregnancy, 40.9% (n = 79/193) pointed out their reluctance, and 16.6% (n = 32/193) indicated that they had no opinion about the subject. Women who were <= 28 weeks of gestation and did not want to have GCT, were asked to explain the reasons of their reluctance. The most frequently indicated reason was the belief that GCT is harmful for their babies and themselves (n = 62/79, 78.5%). Of the women who were >28 weeks of gestation, 37.8% (n = 45/119) had GCT in the ongoing pregnancy, while 62.2% (n = 74/119) did not have GCT. The most frequently indicated reason why women did not have a GCT was the belief that GCT is harmful for themselves and the baby (n = 37/74, 50%). CONCLUSION: This study exposes an important problem - misinformation about 50-g GCT - that carries a dangerous potential for missing the diagnosis of gestational diabetes. Study findings put forth the need for raising awareness among pregnant women and training health-care professionals about the subject.
Keywords: Awareness; gestational diabetes mellitus; glucose challenge test; pregnancy; ASSOCIATION; TOLERANCE; HYPERGLYCEMIA; KNOWLEDGE